Efficacy & Implementation Gaps in the ‘Core Environmental Laws’ of Bangladesh: An Overview (Dhaka University Law Journal, 2022)
Environmental concerns are cross-cutting in nature, touching all sector-specific actions. In recent decades, Bangladesh has been experiencing with loads of environmental issues, leading to persistent deteriorating environmental state. Consequently, the cause of ‘environment conservation’ has been felt to realize and the primary responsibility vests on the Ministry of Environment, Forest and Climate Change and the Department of Environment. Accordingly, the country is in the constant process of internalizing the international environmental commitments into its national regulatory regime. Approximately two hundred national legal instruments are linked, to some extent, with the diverse aspects of environmental governance. Despite the specific responsibilities as allocated to the different governmental agencies through abundant environmental laws, their implementation status is far behind the international standards. Multiple and interconnected reasons fuel the environmental anarchies, obstructing to ensure the sound environmental management in Bangladesh and a threat to sustainable development. Most importantly, the non-integration of various environmental concerns into the developmental action agendas, at the planning, implementing and monitoring stage is the overarching cause. As ‘right to environment’ and ‘environmental justice’ depend on effective environmental legal and policy instruments, this article predominantly attempts to provide an overview of the statutory provisions, efficacy and implementation gaps in those environmental legislations of Bangladesh which are so far officially recognized as ‘core environmental laws’.Dhaka University Law Journal, 2022, 33(1), 73-98